2021
DOI: 10.1002/admi.202101216
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Nanohybrids of 2D Ni‐Cr‐Layered Double Hydroxide Nanosheets Pillared with Polyoxovanadate Anions for High‐Performance Hybrid Supercapacitor

Abstract: In this study, the use of exfoliation‐restacking strategy to prepare mesoporous nanohybrids of 2D Nickel‐chromium‐layered double hydroxide (Ni‐Cr‐LDH) nanosheets pillared with polyoxovanadate (POV) anions (Ni‐Cr‐LDH‐POV) for a high‐performance hybrid supercapacitor (HSC) is demonstrated. The pillaring approach of Ni‐Cr‐LDH monolayers with POV anions via exfoliation‐restacking strategy yields mesoporous ordered layered structure with a high surface area and interconnected network morphology. The pillared hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 76 publications
2
11
0
Order By: Relevance
“…The morphology of CN-5 and NC-L shown in Figure S3 confirms the 2D character of both CN-5 and NC-L. The morphology of NC-L is similar to that reported in a recently published study, which confirms the 2D structure . The TEM images of CN-NCL-2 are shown in Figure a,b, which further confirm the presence of the g-C 3 N 5 nanosheet decorated with NiCr-LDH.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The morphology of CN-5 and NC-L shown in Figure S3 confirms the 2D character of both CN-5 and NC-L. The morphology of NC-L is similar to that reported in a recently published study, which confirms the 2D structure . The TEM images of CN-NCL-2 are shown in Figure a,b, which further confirm the presence of the g-C 3 N 5 nanosheet decorated with NiCr-LDH.…”
Section: Resultssupporting
confidence: 87%
“…Peaks in the range of 890–1690 cm –1 are assigned to the stretching modes of the CN heterocycles . The strong peak at 1365 cm –1 in NC-L is attributed to the bending vibrations of intercalated NO 3 – ions . A carbon dioxide absorption peak at ∼2300 cm –1 is also observed .…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…16,30 Several reports showed that the capacitance relies on a compatibility between the pore size and the ion size. 30,31 Furthermore, the multivalent nature and the small atomic radius help to achieve extra capacitance. Graphene has a small pore size of ∼4.96 nm, which offers a short diffusion length for charge transportation with a low resistance.…”
Section: Resultsmentioning
confidence: 99%